Cell Type-Specific Differentiation Between Indica and Japonica Rice Root Tip Responses to Different Environments Based on Single-Cell RNA Sequencing - Wang, Zhe; Cheng, Daofu; Fan, Chengang; Zhang, Cong; Zhang, Chao; Liu, Zhongmin (Frontiers in Genetics, 2021)
Background: As Oryza sativa ssp. indica and Oryza sativa ssp. japonica are the two major subspecies of Asian cultivated rice, the adaptative evolution of these varieties in divergent environments is an important topic in both theoretical and practical studies. However, the cell type-specific differentiation between indica and japonica rice varieties in response to divergent habitat environments, which facilitates an understanding of the genetic basis underlying differentiation and environmental adaptation between rice subspecies at the cellular level, is little known. Methods: We analyzed a published single-cell RNA sequencing dataset to explore the differentially expressed genes between indica and japonica rice varieties in each cell type. To estimate the relationship between cell type-specific differentiation and environmental adaptation, we focused on genes in the WRKY, NAC and BZIP transcription factor families, which are closely related to abiotic stress responses. In addition, we integrated five bulk RNA sequencing datasets obtained under conditions of abiotic stress, including cold, drought and salinity, in this study. Furthermore, we analyzed quiescent center cells in rice root tips based on orthologous markers in Arabidopsis. Results: We found differentially expressed genes between indica and japonica rice varieties with cell type-specific patterns, which were enriched in the pathways related to root development and stress reposes. Some of these genes were members of the WRKY, NAC and BZIP transcription factor families and were differentially expressed under cold, drought or salinity stress. In addition, LOC_Os01g16810, LOC_Os01g18670, LOC_Os04g52960 and LOC_Os08g09350 may be potential markers of quiescent center cells in rice root tips. Conclusion: These results identified cell type-specific differentially expressed genes between indica-japonica rice varieties that were related to various environmental stresses and provided putative markers of quiescent center cells. This study provides new clues for understanding the development and physiology of plants during the process of adaptative divergence, in addition to identifying potential target genes for the improvement of stress tolerance in rice breeding applications.